Presenting a productivity analysis model for Iran oil industries using Malmquist network analysis - Bazargan, Amir; Najafi, Seyyed Esmaeil; Hoseinzadeh Lotfi, Farhad; Fallah, Mohammad; Edalatpanah, Seyyed Ahmad (Decision Making: Applications in Management and Engineering, 2023)
Organizational performance evaluation is a crucial factor in making strategic decisions for the future. To plan for economic growth, it is important to measure the efficiency and productivity of organizations. Efficiency is a key indicator for evaluating the optimal performance of economic units. Petrochemical companies are vital components of a country's economy and their operations contribute to the growth and progress of different sectors. In countries where the economy relies heavily on this industry, such as ours, petroleum is of utmost importance. Data Envelopment Analysis is a widely used method for measuring productivity. This study aims to analyze the performance evaluation relates to the supply chain of petrochemical companies using the network DEA and Malmquist index. Efficiency and performance indices are calculated for each stage of the process. The study determines the indices through literature review, expert consultation, analysis, and visits to petrochemical companies. The input- and output-oriented multiplier models are used to assess overall and stage efficiencies. Using the efficiency values, the Malmquist productivity index is determined. The study examines unit productivity for the years 1395 to 1398, and the results indicate that most of the units experienced productivity growth during this period.